Ubiquitous Internet in an integrated satellite-terrestrial environment the SUITED solution. - Conforto, P.
The current Internet architecture appears to not be particularly suited to addressing the emerging needs of new classes of users who wish to gain access to multimedia services made available by ISPs, regardless of their location, while in motion and with a guaranteed level of quality. One of the main objectives of so-called next-generation systems is to overcome the limitations of today's available Internet by adopting an approach based on the integration of different mobile and fixed networks. The SUITED project moves in this direction since it aims at contributing to the design and deployment of the global mobile broadband system (GMBS), a unique satellite/terrestrial infrastructure ensuring nomadic users access to Internet services with a negotiated QoS. A description of the main features of the GMBS architecture, characterized by the integration of a multisegment access network with a federated ISP network is given in this article. The GMBS multimode terminal is schematically described, and an overview of the so-called QoS-aware mobility management scheme, devised for such a heterogeneous scenario, is provided
Keywords: GMBS; GMBS architecture; ISP; Internet protocol architecture; Internet service providers; Internet services; SUITED project; WLAN; Federated ISP network; Fixed networks; Global mobile broadband system; Integrated satellite-terrestrial environment; Mobile networks; Multimedia services; Multimode terminal QoS-aware mobility management; Multisegment access network; Negotiated QoS; Network integration; Next-generation systems; Satellite/terrestrial infrastructure; System architecture